Hubungan Tingkat Aktivitas Fisik dan Indeks Massa Tubuh terhadap Daya Tahan Kardiorespirasi pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Ni Komang Ayu Mega Juliyanty; Suyasning Hastiko Indonesiani; Putu Arya Suryanditha (Aesculapius Medical Journal, 2022)
Cardiorespiratory endurance is one indicator of an individual's physical fitness. One of the risk factors for low physical fitness is the low level of physical activity and the body mass index is not ideal. This study aims to determine the relationship between the level of physical activity and body mass index on cardiorespiratory endurance in students of the Faculty of Medicine and Health Sciences, Warmadewa University. This study aims to determine the relationship between the level of physical activity and body mass index on cardiorespiratory endurance in students of the Faculty of Medicine and Health Sciences, Warmadewa University. The method of this study was an analytical observational method with cross sectional design. The number of sampels were 72 students. The activity was measured using Internasional Physical Activity Questionnaire Short Form (IPAQ-SF) and cardiorespiratory endurance was measured using Harvard Step Up Test. Bivariate analysis using Fisher Exact test. The results were showed as follow the highest number of light physical activity, highest of normal body mass index and highest of very poor category of cardiorespiratory endurance. The conclusion could be drawn that there was a significance relationship between the level of physical activity and cardiorespiratory endurance (p<0,05) and there was no relationship between body mass index and cardiorespiratory endurance (p>0,05). It was recommended that the students should improve the physical activity.